Evaluation of Dittrichia viscosa performance in substrates with moderately low levels of As and Cd contamination. (30th October 2020) - Papadia, Paride; Barozzi, Fabrizio; Angilé, Federica; Migoni, Danilo; Piro, Gabriella; Fanizzi, Francesco Paolo; Di Sansebastiano, Gian-Pietro
Abstract: We evaluated the ability of Dittrichia viscosa to extract cadmium (Cd) and arsenic (As) from agarized substrates with moderately low levels of contamination. This plant species spontaneously colonizes contaminated soils and has already been recognized as suitable for metal phytoremediation. D. viscosa retains As mainly in the roots and translocates it in limited amount to the aerial parts. We compared D. viscosa subpopulations to other plant species ( Solalun lycopersicum L., Nicotiana tabacum L. and Daucus carota L.) and observed that their minor cultural needs not always accompanied higher phytoextraction performances. Different subpopulations exhibited different behavior. Based on the results obtained on the analyzed plants, we suggest that D. viscosa is a promising candidate for the phytoextraction of Cd and As from soils with relatively low contamination, cautioning that specific genetic improvements have to be pursued in order to prepare D. viscosa for widespread adoption.